Informe Casa Verde - Carmona-Jiménez, Marvin; Oconitrillo-Obando, Danny; Pineda-Brenes, María; Solano-Brenes, Carlos; Soto-Vargas, Fabiola; Valverde-Rojas, Daniela (Instituto Tecnológico de Costa Rica, 2016)
This investigation represents a part of a larger process of diagnosis concerning the enhancement of a Victorian house located in San Jose city, specifically in Barrio Amón. In this work the importance of a correct approach to the architectural rehabilitation, and the use of a clear methodology is highlighted. We introduce the investigation explaining about the path of Victorian architecture through the world, since its inception until it reaches Costa Rica. Then we focus on exposing Barrio Amón history, in which is located the property where Casa Verde was build. Finally we close this exhibition explaining the spatial configuration of the house and its current state. Also a little bit of the history of the owners of the house until it is bought by the Instituto Tecnológico de Costa Rica. All this as an initial part of the process that is currently underway which aims to culminate in a future architectural rehabilitation.

Esta investigación es parte de un amplio proceso de diagnóstico realizado sobre una casa de estilo Victoriano ubicada en el Barrio Amón, San José, Costa Rica. La esencia de la investigación radica en la rehabilitación arquitectónica aplicada a la arquitectura patrimonial. Para la presente ponencia se hará un recuento sobre los antecedentes del estilo Victoriano y su llegada a Costa Rica. Así mismo se analiza la historia del Barrio Amón, para cerrar con la explicación del inmueble en estudio, desde un enfoque social y arquitectónico.
la influencia del estilo Victoriano en un barrio en San José, Costa Rica
Informe de Investigación. Instituto Tecnológico de Costa Rica. Escuela de Arquitectura y Urbanismo, 2016.
Keywords: Arquitectura patrimonial; Arquitectura Victoriana; Diagnóstico; Historia; Viviendas; Restauración; Rehabilitación arquitectónica